Analysis of Genotype 1b Hepatitis C Virus IRES in Serum and Peripheral Blood Mononuclear Cells in Patients Treated with Interferon and Ribavirin. (3rd July 2014) - Bukowska-Ośko, Iwona; Caraballo Cortés, Kamila; Pawełczyk, Agnieszka; Płoski, Rafał; Fic, Maria; Perlejewski, Karol; Demkow, Urszula; Berak, Hanna; Horban, Andrzej; Laskus, Tomasz; Radkowski, Marek
Abstract : Hepatitis C virus (HCV) highly conserved IRES (internal ribosome entry site) sequence, localized within the 5′-untranslated region (5′UTR), may determine viral properties like replication efficiency and cell tropism. The aim of the present study was to characterize newly emerging 5′UTR variants in serum and peripheral blood mononuclear cells (PBMC) in chronic hepatitis C patients treated with interferon (IFN) and ribavirin and to identify their effect on IRES secondary structures. The study group consisted of 87 patients infected with genotype 1b from whom serum and PBMC samples were collected at 9 time points (before, during, and after treatment). New 5′UTR variants developed in 9 patients. Out of the overall 14 new variants, 9 (64%) were found in PBMC. HCV variants with decreased thermodynamic stability were identified only in PBMC and C183U mutation was the most common one in this compartment. In conclusion, antiviral treatment may favor emergence of new 5′UTR variants both in blood and in PBMC compartments. However, variants developing in the latter compartment were predicted to have lower thermodynamic stability of the IRES secondary structures compared to serum strains. C-U change in position 183, which has not been described previously, might indicate viral adaptation to lymphoid cells.